ANALISIS PENGADAAN BAHAN BAKU DAN NILAI TAMBAH AGROINDUSTRI KERIPIK UBI KAYU DI KECAMATAN WAY JEPARA KABUPATEN LAMPUNG TIMUR - Kusuma, Ekawati Wahyu; Widjaya, Sudarma; Situmorang, Suriaty (Jurnal Ilmu-Ilmu Agribisnis, 2020)
This research aims to analyze the procurement of raw material, added value, and the factors causing inactivity of 18 cassava chips agroindustries. This research was conducted in Way Jepara District, East Lampung Regency in May -July 2018. Respondents were active and non-active cassava chips agroindustries in Way Jepara District. Procurement of raw materials is analyzed using six-component method. The added value is analyzed use Hayami's method, and the cause of inactivity of the 18 cassava chips agroindustries is analyzed qualitatively. The results showed that the procurement of raw materials with six components, namely time, place, price, quantity, quality, and type of active agroindustry is appropriate, because it is in line with the expectations of each active agroindustry. Three active agroindustries have a positive added value (NT>0) can absorb labor, and can increase the income of the community around the agroindustry. The main factors causing the inactivity of 18 cassava chips agroindustries in Way Jepara District in production are less extensive product marketing coverage and low level of demand for the chips produced.Key words: added value, agroindustry, cassava, raw material